DNMT3A R882 Mutations Confer Unique Clinicopathologic Features in MDS Including a High Risk of AML Transformation - Jawad, Majd; Afkhami, Michelle; Ding, Yi; Zhang, Xiaohui; Li, Peng; Young, Kim; Xu, Mina Luqing; Cui, Wei; Zhao, Yiqing; Halene, Stephanie; Al-Kali, Aref; Viswanatha, David; et al. (Frontiers in Oncology, 2022)
DNMT3A mutations play a prominent role in clonal hematopoiesis and myeloid neoplasms with arginine (R)882 as a hotspot, however the clinical implications of R882 vs. non-R882 mutations in myeloid neoplasms like myelodysplastic syndrome (MDS) is unclear. By data mining with publicly accessible cancer genomics databases and a clinical genomic database from a tertiary medical institution, DNMT3A R882 mutations were found to be enriched in AML (53% of all DNMT3A mutations) but decreased in frequency in clonal hematopoiesis of indeterminate potential (CHIP) (10.6%) or other myeloid neoplasms including MDS (27%) (p< .001). Next with the largest cohort of patients with DNMT3A R882 mutant MDS known to date from multiple institutions, DNMT3A R882 mutant MDS cases were shown to have more severe leukopenia, enriched SRSF2 and IDH2 mutations, increased cases with excess blasts (47% vs 22.5%, p=.004), markedly increased risk of AML transformation (25.8%, vs. 1.7%, p=.0001) and a worse progression-free survival (PFS) (median 20.3, vs. >50 months, p=.009) than non-R882 mutant MDS cases. DNMT3A R882 mutation is an independent risk factor for worse PFS, and importantly the differences in the risk of AML transformation between R882 vs. non-R882 mutant patients cannot be explained by different treatment approaches. Interestingly the higher risk of AML transformation and the worse PFS in DNMT3A R882 mutant MDS cases are mitigated by coexisting SF3B1 or SRSF2 mutations. The unique clinicopathologic features of DNMT3A R882 mutant MDS shed light on the prognostic and therapeutic implications of DNMT3A R882 mutations.